Household debt, liquidity constraints and the interest rate elasticity of private consumption - Samu Kärkkäinen; Aino Silvo (Bank of Finland, 2023)
We study whether the level of household indebtedness is related to the interest rate elasticity of private consumption. Looking at Finnish aggregate data, we find no robust evidence of increased interest rate elasticity of private consumption even as the household sector's debt-to-income ratio has almost doubled in the past 20 years. Estimates based on the household-level Finnish Wealth Survey suggest that the share of liquidity-constrained households has declined over the same time period, which may have contributed towards muting the sensitivity of private consumption to interest rates even as aggregate debt of the household sector has grown significantly. Our results are consistent with the key role played by heterogeneity in credit and liquidity constraints in driving aggregate consumption and debt dynamics. Other factors behind muted responses of consumption to interest rates may include the recent low interest rate period, which has muted the cash-flow channel of monetary policy, and possible asymmetric effects of monetary policy.
URN:NBN:fi-fe2023042538658
Keywords: E21; E52; G51; 330; consumption; interest rates; household debt; liquidity constraints